Evaluasi Kebijakan Pendidikan - Naila Nur ‘Azizah; Meysihinur; Aziza, Miftah (Prodi Pendidikan Agama Islam, 2023)
This paper explains several things related to the evaluation of educational policies. This study used a qualitative research approach with a type of library (library research). Sources of data taken in this study are scientific journals and articles that support and are relevant to the title of this paper. A process of implementing education policy is inseparable from the need to get special attention. The elements in it have several deficiencies that need improvement. Starting from legitimacy, formulation, and its implementation in society. Therefore it is necessary to do an evaluation in order to avoid failure in educational policies. Evaluation of educational policies serves to measure how much the quality of spending on a policy is and provides input to the parties involved. The purpose of writing this paper is to know the meaning of educational policy evaluation, the objectives and functions of educational policy evaluation, as well as models and approaches in evaluating educational policies.